Medullomyoblastoma: A rare case in an unusual location in an atypical age group - Bansal, Sumit; Borkar, Sachin; Suri, Ashish; Sharma, Mehar; Mahapatra, Ashok (Asian Journal of Neurosurgery, 2016)
Medullomyoblastoma is a variant of medulloblastoma with an aggressive course. It is typically seen in children less than 10 years of age and usually arises from the cerebellar vermis. Authors report an unusual case of medullomyoblastoma arising from the right middle cerebellar peduncle in an adult patient and pertinent literature is reviewed regarding this uncommon entity.
Keywords: cerebellar peduncle; medulloblastoma; medullomyoblastoma; posterior fossa tumors